Introducing Large Genomic Deletions in Human Pluripotent Stem Cells Using CRISPR‐Cas3. Issue 2 (7th February 2022) - Hou, Zhonggang; Hu, Chunyi; Ke, Ailong; Zhang, Yan
Abstract: CRISPR‐Cas systems provide researchers with eukaryotic genome editing tools and therapeutic platforms that make it possible to target disease mutations in somatic organs. Most of these tools employ Type II (e.g., Cas9) or Type V (e.g., Cas12a) CRISPR enzymes to create RNA‐guided precise double‐strand breaks in the genome. However, such technologies are limited in their capacity to make targeted large deletions. Recently, the Type I CRISPR system, which is prevalent in microbes and displays unique enzymatic features, has been harnessed to effectively create large chromosomal deletions in human cells. Type I CRISPR first uses a multisubunit ribonucleoprotein (RNP) complex called Cascade to find its guide‐complementary target site, and then recruits a helicase‐nuclease enzyme, Cas3, to travel along and shred the target DNA over a long distance with high processivity. When introduced into human cells as purified RNPs, the CRISPR‐Cas3 complex can efficiently induce large genomic deletions of varying lengths (1‐100 kb) from the CRISPR‐targeted site. Because of this unique editing outcome, CRISPR‐Cas3 holds great promise for tasks such as the removal of integrated viral genomes and the interrogation of structural variants affecting gene function and human disease. Here, we provide detailed protocols for introducing large deletions using CRISPR‐Cas3. We describe step‐by‐step procedures for purifying the Type I‐E CRISPR proteins Cascade and Cas3 from Thermobifida fusca, electroporating RNPs into human cells, and characterizing DNA deletions using PCR and sequencing. We focus here on human pluripotent stem cells due to their clinical potential, but these protocols will be broadly useful for other cell lines and model organisms for applications including large genomic deletion, full‐gene or ‐chromosome removal, and CRISPR screening for noncoding elements, among others. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Expression and purification of Tfu Cascade RNP Support Protocol 1 : Expression and purification of TfuCas3 protein Support Protocol 2 : Culture of human pluripotent stem cells Basic Protocol 2 : Introduction of Tfu Cascade RNP and Cas3 protein into hPSCs via electroporation Basic Protocol 3 : Characterization of genomic DNA lesions using long‐range PCR, TOPO cloning, and Sanger sequencing Alternate Protocol : Comprehensive analysis of genomic lesions by Tn5‐based next‐generation sequencing Support Protocol 3 : Single‐cell clonal isolation